Regionalisation Of Hospital Infrastructure In The Eastern Transvaal Area - Crisp, Nicholas Gilmour (My University, 1991)
The extremely complex fragmentation of health services in the greater South Africa has lead to confusion, duplication and uncoordinated planning. This study assesses the hospital component of the health services in one discrete geographical area where service responsibilities are particularly complex. Each of the hospitals identified within the study area was visited and, after a short conducted tour, detailed information was obtained on a standard questionnaire during interviews with senior hospital personnel. Final detail was obtained by inspection of various functional components in each hospital. Proposals regarding the process of regionalising the hospital services in a future post-apartheid era (when political boundaries, particularly homeland boundaries, have disappeared and the health services can be rationalised under a unified health authority) are made. The major finding is that, while some expansion is needed, the existing facilities can be reorganised into a functional complex at minimal cost and limited disruption of services.
A Dissertation Submitted to the Faculty of Medicine University of the Witwatersrand, Johannesburg for the Degree of Master of Medicine (Community Health)
Keywords: Hospitals South Africa.